Building Digital Governance Integration Internal Audit Through Strategy Application Programming Interface (API): Study on BUMN Holding Survey Services (IDSurvey) - Rahman, Abdur; Yopan, Muhamad; Fitriati, Rachma (Manunggal Halim Jaya, 2025)
This article discusses the Indonesian Classification Bureau, which needs to integrate digital governance from the application Internal Audit – Internal Audit Portal (SPI) to the application Human Resource Management System (HRMS) for the automation of Key Performance Indicator (KPI) results. However, until now, the Society still uses manual calculations to display Corporate, Work Unit, and Individual KPI, which causes delays in reports to shareholders and disbursing team member benefits. This research uses a qualitative method with the Soft Systems Methodology (SSM) approach to analyze digital governance utilizing the SPI portal application in the Internal Audit Division. The results show that no tools automate KPI values from the SPI Portal application to the HRMS system. This research can provide recommendations for making SPI Portal SOP policies that can measure and monitor performance, and the results can be sent directly to the HRMS systems. This research contributes to manually changing the KPI assessment system into a system that can produce accurate, transparent, and equitable results.